ON THE UNIQUENESS OF ALGEBRAIC CURVES - Bayramyan, V.H.; Hakopian, H.A.; Toroyan, S.Z. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
It is well-known that N -1 n-independent nodes uniquely determine curve of degree n, where N = (1/2)(n + 1)(n + 2). We are interested in finding the minimal number of n-independent nodes determining uniquely curve of degree k≤1. In this paper we show that this number for k=n-1 is N-4.